Risk factors for surgical site infections following microwave ablation of the uterus: a retrospective cohort study - Chuan Chen; Hanshu Wu; Xinyu Wang; Ying Peng; Ying Peng’; Lei Lei; Yangyang Zhao; Gang Chen (BMC Women's Health)
Abstract Purpose As microwave ablation (MWA) becomes an increasingly popular treatment for gynecological diseases, complications such as surgical site infections (SSIs) have emerged as critical concerns, particularly in high-risk patient populations. Identifying independent risk factors for SSIs is essential to implement effective preventive measures and enhance patient outcomes. Methods This retrospective study included women aged 18–55 with a diagnosis of uterine myoma or adenomyosis who underwent MWA at the First Affiliated Hospital of the University of Science and Technology of China between December 2020 and November 2023. Patient selection criteria included undergoing laparoscopic MWA by our team and providing written informed consent. The Kolmogorov-Smirnov test was used to assess the normality of continuous variables, and statistical analyses were performed using the Student’s t-test, Mann-Whitney U test, and χ2 test. Multivariate logistic regression identified potential predictors for SSIs. Results In this study, SSIs were observed in 7.58% of patients, with prolonged surgical duration and abdominal adhesions identified as significant independent risk factors. Conclusion This study provides insights into SSIs following MWA surgery in a Chinese population, highlighting specific risk factors that could inform preventive strategies to improve surgical outcomes and patient safety.